2020
DOI: 10.24093/awej/vol11no4.19
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Grammar Teaching in a Saudi EFL Context: Teachers’ Perceptions and Practices

Abstract: In language, meaning is conveyed and received through words and grammar. A phrase or a sentence is not a random collection of words. In the absence of grammar, words hang together without any real meaning. Thus, grammar plays an essential role in language teaching. With adequate grammar explanations in meaningful contexts and practice, some serious errors in learners' language can be avoided. This study aimed at examining the relationship between teachers’ perceptions of grammar teaching and their actual prac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These strategies are outdated now (Al Zahrani & Elyas, 2017;Alnofaie, 2013b;Bunaiyan, 2019;Makhlouf, 2021). The Saudi schools follow the grammar-translation method (Abduh & Algouzi, 2020;Eisa, 2020;Milawati, 2019) and practice code-switching (Alkatheery, 2014;Almansour, 2016;Alshugithri, 2015). Both the method and the practice require the use of Arabic in the classroom.…”
Section: The Present Condition Of Efl Learningmentioning
confidence: 99%
“…These strategies are outdated now (Al Zahrani & Elyas, 2017;Alnofaie, 2013b;Bunaiyan, 2019;Makhlouf, 2021). The Saudi schools follow the grammar-translation method (Abduh & Algouzi, 2020;Eisa, 2020;Milawati, 2019) and practice code-switching (Alkatheery, 2014;Almansour, 2016;Alshugithri, 2015). Both the method and the practice require the use of Arabic in the classroom.…”
Section: The Present Condition Of Efl Learningmentioning
confidence: 99%
“…They, also, found that relying solely on communicative tasks without the necessary focus on form might not help EFL students achieve desired levels of grammatical accuracy. Through a questionnaire and classroom observations, Abduh and Algouzi (2020) found out that Saudi EFL teachers tended to adopt traditional methods while teaching grammar, and these conventional methods usually overlooked the role of grammar in achieving communicative competence. In Iraq, Ajaj's (2022) descriptive study highlighted Arab EFL learners' and teachers' misconceptions about grammar role as a major obstacle in its teaching and learning.…”
Section: Difficulties Of Learning and Teaching Efl Grammarmentioning
confidence: 99%